Multiple Patient Casualty Scenarios: A Measurement Tool for Teamwork. Issue 6 (December 2018) - Marlow, Shannon L.; Bedwell, Wendy L.; Zajac, Stephanie; Reyes, Denise L.; LaMar, Michelle; Khan, Saad; Lopreiato, Joseph; Salas, Eduardo
Abstract : Introduction: Teamwork is a critical aspect of patient care and is especially salient in response to multiple patient casualties. Effective training and measurement improve team performance. However, the literature currently lacks a scientifically developed measure of team performance within multiple causality scenarios, making training and feedback efforts difficult. The present effort addresses this gap by integrating the input of subject matter experts and the science of multicasualty teams and training to (1) identify overarching teamwork processes and corresponding behaviors necessary for team performance and (2) develop a behavioral observation tool to optimize teamwork in multicasualty training efforts. Method: A search of articles including team performance frameworks associated with team training was conducted, leading to the identification of a total of 14 articles. Trained coders extracted teamwork processes and the corresponding team behaviors indicative of effective performance from these articles. Five subject matter experts were interviewed using the critical incident technique to identify additional behaviors. Results: Team situation awareness, team leadership, coordination, and information exchange emerged as the four core team processes required for team performance in scenarios with multiple patient casualties. Relevant behaviors and subbehaviors within these overarching processes were identified to inform a pilot behavioral framework of team performance. Conclusions: The processes and associated behaviors identified within this effort serve as scientifically grounded behaviors of team performance in the case of multiple patient casualties simulated training scenarios. Future work can use and further refine these results to ensure that measures of team performance are grounded in specific, observable, and scientifically delineated behaviors. Abstract : Supplemental digital content is available in the text.